Sengoku youko. 6 - Mizukami, Satoshi (Tokyopop Inc., 2024)
The world is divided into two factions: humans and monsters called katawara. Despite being a katawara, Tama loves humans and vows to protect them from evil, even if it means fighting her own kind. Her brother Jinka, however, hates humans, despite mostly being one. The siblings are joined by a cowardly swordsman named Shinsuke, who wants to learn how to become strong. The people they meet, places they see, and creatures they battle will be legendary!